1989
DOI: 10.1002/anr.1780320116
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial outcomes of the arthritis self‐management course are not adequately explained by behavior change

Abstract: Evaluation of the Arthritis Self-ManagementCourse revealed significant positive changes in the practice of behaviors that were taught and in health outcomes. However, utilizing a variety of statistical techniques, we were able to demonstrate only weak associations between changes in behavior and changes in health status. This suggests the need to examine the mechanisms by which health education affects heaMh status.As do other persons who have chronic and disabling illnesses, the person who has arthritis plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
1
7

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(112 citation statements)
references
References 8 publications
6
98
1
7
Order By: Relevance
“…We examined the WTW retention/attrition patterns, explored the predictors of retention, and described the reasons women gave for leaving the study. Through these discoveries, it was our hope that barriers to retaining participants in the study might be identified that could lead to the design of strategies to overcome them.Overall, attrition patterns in WTW (18.9%) compared favourably with previous research--not unlike attrition rates reported in other similar intervention studies of five to six months' duration (17%, 19%, and 17%) (Lorig, Ritter, & Gonzalez, 2003;Lorig et al, 1989;Lorig et al, 1999), and the bulk of attrition was found early during the study period. This finding contrasts with others who have found that attrition is usually seen toward the end of a study or throughout the study, with cumulative loss occurring with successive data-collection efforts (Marcellus, 2004).…”
supporting
confidence: 76%
“…We examined the WTW retention/attrition patterns, explored the predictors of retention, and described the reasons women gave for leaving the study. Through these discoveries, it was our hope that barriers to retaining participants in the study might be identified that could lead to the design of strategies to overcome them.Overall, attrition patterns in WTW (18.9%) compared favourably with previous research--not unlike attrition rates reported in other similar intervention studies of five to six months' duration (17%, 19%, and 17%) (Lorig, Ritter, & Gonzalez, 2003;Lorig et al, 1989;Lorig et al, 1999), and the bulk of attrition was found early during the study period. This finding contrasts with others who have found that attrition is usually seen toward the end of a study or throughout the study, with cumulative loss occurring with successive data-collection efforts (Marcellus, 2004).…”
supporting
confidence: 76%
“…A partly controllable disease, rheumatoid arthritis (RA), is characterised by a progressive and unpredictable course, with intermittent periods of disease flare and remission. By adjusting rest, exercise and medication to the changing disease activity, patients can partly alleviate their pain, the extent of joint destruction and physical functioning (Lorig, Seleznick, Lubeck, Ung, Chastain, & Holman, 1989). In contrast to IDDM patients, self-care is less compelling and less effective for RA patients.…”
Section: Controllability Of Chronic Diseasementioning
confidence: 99%
“…Other studies have also found associations between perceived self-efficacy and health status among arthritis patients (9,(15)(16)(17)(18). The Arthritis Self-Management Program (ASMP) developed by Kate Lorig and colleagues has been shown to result in increased knowledge, more consistent performance of health practices, and reductions in pain (12,19,20). Reductions in pain and in number of visits to physicians persisted up to 4 years after participation in the ASMP, despite the increasing physical disability of the patients (21).…”
Section: Introductionmentioning
confidence: 99%